Effects of particle size and composition of sawdust/carbon from rice husk on the briquette performance - Anggraeni, S. (Taylor's University, 2021)
This study investigated effects of particle size and composition of sawdust (SWs) and carbon from rice husk (CRHs) on briquette performance. In the experiments, briquettes with 10, 30, 50, 70, 90 of CRHs and a specific particle size (i.e., 250, 500, 1000, and 2000 Î¼m) were prepared and starch paste was used as binder. To support the analysis, moisture content in wet basis and dry basis, bulk density, compressed density, relaxed density, compressed ratio, relaxation ratio, water resistance capacity, durability index, burning rate, and specific fuel consumption were determined. The experimental results showed that a low concentration of CRHs resulted in high bulk, compressed, relaxed density values, and increases in relaxation ratio of the briquettes. However, a high concentration of CRHs resulted in decreases in compaction ratio, water resistance, durability, and relatively not favourable for briquetting. Cooperative combustion was positively affecting the burning rate and specific fuel consumption in 10, 50, 90 of CRHs briquette under the influence of rapid burning. Finer particle size of briquette resulted in increases in moisture content on a wet basis and compaction ratio. On the other hand, large particle size led to increases in bulk, compressed, relaxed densities, relaxed ratio, moisture content on a dry basis, water resistance, durability, specific fuel consumption, and burning rate. This study demonstrated new information on utilization of agricultural wastes as a renewable energy fuel. Â© School of Engineering, Taylor's University